Lieutenant Owen William Steele of the Newfoundland Regiment : diary and letters - Steele, Owen William (McGill-Queen's University Press, 2002)
"Lieutenant Owen William Steele volunteered for the famed Newfoundland Regiment in late summer 1914. His war diary, begun as he embarked for England, relates the experiences of his regiment training on Salisbury Plain and in Scotland, baptism of fire at Gallipoli, recuperation in Egypt, and, finally, the battlefields of France. Along the way his sense of adventure turns to a growing weariness with war, a desire to return home, and an underlying hope that he will survive. His diary ends twenty-two months later on the eve of the Battle of the Somme at Beaumont Hemel, a few days before his death."--Jacket